2021
DOI: 10.3390/ijerph18052529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anti-Rheumatic Treatment on the Periodontal Condition of Rheumatoid Arthritis Patients

Abstract: Periodontitis, a bacterial-induced infection of the supporting soft and hard tissues of the teeth (the periodontium), is common in patients with rheumatoid arthritis (RA). As RA and periodontitis underlie common inflammatory pathways, targeting the progression of RA might mediate both periodontitis and RA. On the other hand, patients with RA on immunosuppressive medication have an increased risk of infection. Therefore, the objective of this longitudinal observation study was to assess the effect of methotrexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…Also, RA patients can have periods of disease remission/relapse and this way, the systemic inflammation will be altered increasing CRP levels 36 . The results agree with other studies 22,27,[37][38][39] , but systematic reviews have shown no effect of NSPT on ACPAs and RF, consequently, producing contrasting conclusions 23,40 . It has been suggested that NSPT has systemic effects by reducing periodontal inflammatory sources 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Also, RA patients can have periods of disease remission/relapse and this way, the systemic inflammation will be altered increasing CRP levels 36 . The results agree with other studies 22,27,[37][38][39] , but systematic reviews have shown no effect of NSPT on ACPAs and RF, consequently, producing contrasting conclusions 23,40 . It has been suggested that NSPT has systemic effects by reducing periodontal inflammatory sources 21 .…”
Section: Discussionsupporting
confidence: 91%
“…This might be due to the limited access to biological treatment for many patients in Indonesia because of the high costs [ 33 ]. Antirheumatic treatment seems to have a negligible influence on the periodontal condition of RA patients, and to not have an influence on the subgingival presence of Pg and Aa, accordingly [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another study has contradictory results and states that metotrexate and anti-TNF treatment has an insignificant effect on the periodontal status of RA subjects. [80].…”
Section: Dmardsmentioning
confidence: 99%